ANALISIS PENILAIAN TINGKAT KESEHATAN BANK SYARIAH DENGAN METODE IBADAH, MUAMALAH, AMANAH, IHSAN (IMAN) - Heppy Okyanta (Jurnal Akuntansi Aktual, 2017)
The purpose of the study is to describe effectiveness of IMAN method to evaluate risk base bank rating of “X” Islamic Bank. The study uses a qualitative approach with discriptive method. Source of the data is obtained from interviews, observation, and study the documentation on the reports from “X” Islamic Bank. The results showed that the financial aspects such as capital, the level of rentability and liquidity of “X” Islamic Bank have been sufficient, however its level of officiency has yet been sufficient that is 97.33% above the average standard of banking. The religious teaching aspect of “X” Islamic Bank that is “amar makruf nahi munkar” remains within worldly level and has yet discussed divine consciousness domain. Client’s lack of ability to understand the concept of Islamic Bank becomes the indicator. Such phenomenon shows that religious teaching aspect of “X” Islamic Bank should be improved. Furthermore, “X” Islamic Bank as Islamic business organization still emphasize on profit oriented instead of zakat oriented.Keywords:Risk Base Islamic Bank Rating, IMAN